Anti-Locality and Preposition Stranding in a Variety of Ontario French - Therrien, Ray (Université d'Ottawa / University of Ottawa, 2023)
This thesis investigates and documents the existence of preposition stranding in a dialect of Canadian French. The French spoken in the small Franco-Ontarian town of Lafontaine (LFF) allows prepositions to be stranded (i.e. without a following overt complement) in various scenarios. Taking bona fide P-stranding to be derivable only via leftward movement of prepositional complements, I show that LFF has true P-stranding equivalent to that observed in English. I argue that although LFF parallels Standard French in having orphan prepositions–where this phenomenon is best analyzed as non-movement derived P-stranding with the gap following the preposition being the instantiation of a null pronoun (Authier 2016; Zribi-Hertz 1984)–it is incontrovertible that P-stranding takes place under syntactic movement in LFF (e.g. wh-movement). Following Abels (2003b, 2012), I assume that prepositions constitute phase heads and their complements cannot be extracted without violating the principle of anti-locality. My central argument in this thesis is that in order to void violations of anti-locality, PPs in P-stranding languages must contain an extra layer of structure between prepositions and their complements in order to allow extraction. Evidence for this extra layer of structure is found in LFF in the form of the invariant morpheme de-nwhich appears on the prepositions dans, sur and sous when these are used in stranding constructions (e.g. dedans). Again, following Abels (2012), I label the de- element that appears on these prepositions under stranding as a ‘DR-morpheme’; this morpheme constitutes the head of a DRP which intervenes between prepositions and their complements, allowing extraction. I further show that evidence for the existence of bona fide P-stranding in LFF comes in the form of the ability to strand prepositions under ellipsis in this dialect. LFF, like English, allows prepositions to be stranded in swiping constructions, where swiping is a sub form of sluicing wherein a prepositions and its wh-complement surface in inverse order (e.g. `who from’/qui de) as the sole remnants of ellipsis. Given the existence of swiping in LFF, I discuss certain ramifications this has for current theories of sluicing and swiping, ultimately arguing that swiping in LFF is best analyzed as being derived via deleting prosodically redundant material between a wh-phrase which has moved to the left periphery, and its selecting preposition which has been left stranded in its base position.
Keywords: Canadian French; Preposition stranding; Structure of PP; Ellipsis; Sluicing; Swiping